Investment Climate Reform : An Independent Evaluation of World Bank Group Support to Reforms of Business Regulations - Independent Evaluation Group (World Bank Group, Washington, DC, 2015)
Private firms are at the forefront of the development process providing more than 90 percent of jobs, supplying goods and services, and representing a significant source of tax revenues. Their ability to grow, create jobs, and reduce poverty depends critically on a well-functioning investment climate defined as the policy, legal and institutional arrangements underpinning the functioning of markets and the level of transaction costs and risks associated with starting, operating and closing a business. The World Bank Group has been providing extensive support to investment climate reforms—having supported over the period FY07–13, 819 projects with investment climate interventions in 119 countries for a total estimated value of $3.7 billion. This evaluation is designed to assess the relevance, effectiveness, and social value as it relates to concerns for inclusion and shared prosperity of World Bank Group support to investment climate reforms.